In Vivo Antimalarial Activity of 80% Methanol and Aqueous Bark Extracts of Terminalia brownii Fresen. (Combretaceae) against Plasmodium berghei in Mice - Hana Biruk; Biruk Sentayehu; Yonatan Alebachew; Wondmagegn Tamiru; Abebe Ejigu; Solomon Assefa (Biochemistry Research International)
Background. Despite a substantial scientific progress over the past two decades, malaria continues to be a worldwide burden. Evergrowing resistance towards the currently available antimalarial drugs is a challenge to combat malaria. Medicinal plants are a promising source of new drugs to tackle this problem. Thus, the present study aimed at evaluating the antiplasmodial activity of Terminalia brownii in Plasmodium berghei infected mice. Methods. A 4-day suppressive test was employed to evaluate the antimalarial effect of 80% methanol and aqueous bark extracts of T. brownii against P. berghei in Swiss albino mice. Results. The in vivo acute toxicity test indicated that both extracts of T. brownii did not cause mortality. The 4-day early infection test revealed that the 80% methanol and aqueous extracts exhibited a significant inhibition of parasitemia p<0.001 compared to negative control. The maximum level of chemosuppression (60.2%) was exhibited at 400 mg/kg dose of 80% methanol extract. Moreover, the 80% methanol extract showed a significant p<0.001 attenuation of anemia associated with infection in a dose-dependent manner. The aqueous extract, on the other hand, exhibited a percent inhibition of 51.1% at the highest dose (400 mg/kg/day). Conclusion. The present study indicated that hydromethanolic and aqueous bark extracts of T. brownii possess a promising antimalarial activity, with higher effect exhibited by the hydromethanolic extract.